Tecnologia de aplicação de produtos fitossanitários na cafeicultura - Gitirana Neto, Jefferson (2015)
Coffee crop is an important agricultural activity in Brazil that faces great technological challenges, especially for pesticide application. This study was done to determine the effect of different spray nozzles, mixture volumes and side sprayer bar, as well as deposition of mixture on biological efficacy of control of leaf miner Leucoptera coffeella (Guérin-Méneville). Also, the performance of hydropneumatic equipment was evaluated, with or without electrostatic charge, on coffee crop in the savannah, and the deposition of the mixture in hillside crop. Three independent studies were done, one in Uberlândia/MG (savannah coffee), one in Rio Paranaíba/MG (savannah coffee) and one in Nova Resende/MG (hillside coffee). Mixture deposition and penetration in lower, medium and upper canopy and run-off to soil were evaluated by the addition of the tracer Brilliant Blue FD&C Blue n.1, for quantification by spectrophotometry. Control efficacy of leaf miner was evaluated by the percentage of live larvae. Results indicated that the use of the side bar increased mixture deposition in the lower canopy; however, deposition in the middle third of the plant was reduced, and run-off increased. The hollow cone sprayer tip with air induction also increased run-off. Electrostatic spraying in hydropneumatic equipment resulted in greater mixture deposition in the lower canopy of coffee. Sprayer Twister, manufactured by Montana, coupled with directed air ducts, had better performance in plant lower and medium canopy than Arbus, from Jacto, with nozzles placed along side arches. Mixture volume used in hydropneumatic sprayers with no electrostatic charge (200 to 500 L ha-1) did not affect mixture deposition on plants and losses to soil, which were smaller with the use of electrostatic sprayer. Electrostatic sprayer, in hillside coffee plantation, at 200 L ha-1, with the use of copolymer polyester-polymethyl siloxane adjuvant, increased mixture deposition in adult coffee plants.